FORMING OF REASONABLE SYSTEM OF SOCIAL-ECONOMIC DEVELOPMENT OF REPUBLIC OF SOUTH OSSETIA IN CONTEXT OF NATIONAL ECONOMIES GLOBAL TURBULENCE - Dzambolat Tadtaev; Jurij Zhevora (Вестник Северо-Кавказского федерального университета, 2022)
The main objective of the study is to maintain an effective management of the national economy development. The result of the study is a conceptual background necessary to follow while building social-economic system of South Ossetia that allows to hypothetically achieve optimal development of the national economy. Basic model of economic mechanism for revival of national economy is provided.